2018
DOI: 10.1080/03008207.2018.1439486
|View full text |Cite|
|
Sign up to set email alerts
|

Release of pro-inflammatory cytokines from muscle and bone causes tenocyte death in a novel rotator cuff in vitro explant culture model

Abstract: Overall, this model presents an innovative approach to understandingrotator cuff injury and tenocyte mechanobiology in a clinically-relevant tendon structure. Our model can be a powerful tool to investigate how mechanical and biological stimuli can alter normal tendon health and lead to tendon degeneration, and may provide a testbed for therapeutics for tendon repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 75 publications
6
32
0
Order By: Relevance
“…The levels of pro‐inflammatory cytokines produced from this muscle/bone injury are consistent with those previously measured in human synovial fluid immediately following various joint injuries . We also demonstrated that exposing otherwise healthy flexor explants (tendon‐only cultures) to conditioned medium (CM) collected from this injury model, or to individual pro‐inflammatory cytokines (IL‐1β, IL‐6, and TNF‐α), resulted in similar degenerative changes, indicating the role of inflammatory mediators in inducing tissue damage and degeneration …”
supporting
confidence: 85%
See 4 more Smart Citations
“…The levels of pro‐inflammatory cytokines produced from this muscle/bone injury are consistent with those previously measured in human synovial fluid immediately following various joint injuries . We also demonstrated that exposing otherwise healthy flexor explants (tendon‐only cultures) to conditioned medium (CM) collected from this injury model, or to individual pro‐inflammatory cytokines (IL‐1β, IL‐6, and TNF‐α), resulted in similar degenerative changes, indicating the role of inflammatory mediators in inducing tissue damage and degeneration …”
supporting
confidence: 85%
“…This model system contains uninjured supraspinatus tendon connected to pieces of bone and muscle in a three‐dimensional (3D) explant model. In our previous study, we reported that acute trauma to the bone and muscle induces a remarkable release of pro‐inflammatory cytokines from both tissues, and that there was a rapid loss of tenocyte viability in the first 48 h following this injury . The levels of pro‐inflammatory cytokines produced from this muscle/bone injury are consistent with those previously measured in human synovial fluid immediately following various joint injuries .…”
supporting
confidence: 85%
See 3 more Smart Citations